PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI UPTD BALAI LATIHAN KERJA KOTA PROBOLINGGO - Hakim, Lukman (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This research aims to analyze the influence of competence and compensation on performance through job satisfaction of UPTD employees at the Probolinggo City Job Training Center. This research is explanatory research with a quantitative approach. Hypothesis testing is carried out using path analysis. The results of this research show that: (1). Competency does not have a significant influence on job satisfaction of UPTD employees at the Probolinggo City Job Training Center, (2). Competency has a significant influence on the performance of UPTD employees at the Probolinggo City Job Training Center, (3). Work compensation has a significant influence on job satisfaction of UPTD employees at the Probolinggo City Job Training Center, (4). Work compensation has a significant influence on the performance of the Probolinggo City Job Training Center Employee UPTD, (5). Job satisfaction does not have a significant influence on the performance of UPTD employees at the Probolinggo City Job Training Center, (6). Competency does not have a significant effect on performance through job satisfaction of UPTD employees at the Probolinggo City Job Training Center, (7). Work compensation does not have a significant effect on performance through job satisfaction of UPTD employees at the Probolinggo City Job Training Center.